A new finite-time cooperative control algorithm for uncertain multi-agent systems. Issue 5 (4th April 2019) - Song, Ge; Shi, Peng; Wang, Shuoyu; Pan, Jeng-Shyang
ABSTRACT: In this paper, the problem of fixed-time consensus tracking control is investigated for multi-agent networks with input uncertain dynamics under the undirected graph. First, a nonsingular terminal sliding mode manifold is proposed, with which the convergence time is globally bounded irrelevant to initial states. Then, with the aid of the observer method and sliding mode technique, the distributed nonsingular controller is designed for the underlying system to ensure that the consensus tracking errors go into sliding mode manifold and converge to origin within a desired time. Finally, examples are presented to verify the validity of the new control strategy.